MIOTA-Based Filters for Noise and Motion Artifact Reductions in Biosignal Acquisition - Fabian Khateb; Pipat Prommee; Tomasz Kulej (My University, 2022)
This paper presents a new low-voltage CMOS structure for operational transconductance amplifier (OTA) exploiting the bulk-driven, the self-cascode and the multiple-input transistor techniques (MI). The multiple-input OTA (MIOTA) circuit operates in subthreshold region using 0.5V supply voltage and offers enhanced linearity. The MIOTA is developed for biopotential signal as well as electrocardiogram (ECG) signal processing circuit and it is exploited to design a 5th-order Chebyshev low-pass and 3rd-order band-pass filters with a dynamic range (DR) of 57.6 dB and 60.4 dB, and nanopower consumption of 50 nW and 60 nW, respectively. Due to the electronic tuning of cut-off frequency, the low-pass and band-pass filters are suitable for random noise and motion artifact noise reductions in biopotential signals. The circuits were designed in Cadence environment using the standard N-well $0.18~\mu \text{m}$ TSMC CMOS technology. Intensive post-layout simulation results along with the process, voltage, temperature analysis (PVT) and Monte Carlo (MC) prove the robustness of the design. The chip area of the proposed MIOTA is 0.00725 mm2 ( $118~\mu \text{m}\,\,\times 61.5\,\,\mu \text{m}$ ). Compared with standard OTA the MIOTA offers simplification of filter topology and reduced number of active elements. In order to demonstrate these advantages, the MIOTA-based filter was also build using commercially available OTA LT1228. The experimental results of OTA LT1228 confirm both the filter functionality and the advantages of the proposed MIOTA.
Keywords: Biosignal; Artifact (error); Analog and Mixed-Signal Circuit Design